2023
DOI: 10.3390/cells12182304
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and Its Derivates as Potential Photosensitizers in the Photodynamic Treatment of Skin Cancers

Małgorzata Insińska-Rak,
Marek Sikorski,
Agnieszka Wolnicka-Glubisz

Abstract: Riboflavin, a water-soluble vitamin B2, possesses unique biological and physicochemical properties. Its photosensitizing properties make it suitable for various biological applications, such as pathogen inactivation and photodynamic therapy. However, the effectiveness of riboflavin as a photosensitizer is hindered by its degradation upon exposure to light. The review aims to highlight the significance of riboflavin and its derivatives as potential photosensitizers for use in photodynamic therapy. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
(189 reference statements)
0
3
0
Order By: Relevance
“…However, this compound photodegrades, reducing its effect been reported, however, that some of its photodegradation produc (12), are photosensitizers [88], which could be advantageous for aP Due to its structural similarity to hypericin, together with its ability to absorb light in the UV-visible region, it has drawn attention as a PS for aPDT [87]. Work by Wang et al showed that aloe-emodin-mediated aPDT is effective against infections caused by A. baumannii [29].…”
Section: Natural Occurring Pss Used Against Fish Bacterial Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this compound photodegrades, reducing its effect been reported, however, that some of its photodegradation produc (12), are photosensitizers [88], which could be advantageous for aP Due to its structural similarity to hypericin, together with its ability to absorb light in the UV-visible region, it has drawn attention as a PS for aPDT [87]. Work by Wang et al showed that aloe-emodin-mediated aPDT is effective against infections caused by A. baumannii [29].…”
Section: Natural Occurring Pss Used Against Fish Bacterial Pathogensmentioning
confidence: 99%
“…However, this compound photodegrades, reducing its effec been reported, however, that some of its photodegradation produc (12), are photosensitizers [88], which could be advantageous for a However, this compound photodegrades, reducing its effectiveness as a PS. It has been reported, however, that some of its photodegradation products, such as lumichrome (12), are photosensitizers [88], which could be advantageous for aPDT.…”
Section: Natural Occurring Pss Used Against Fish Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…153 Similarly, the use of riboflavin and its derivates in PDT has opened the door to treating skin cancers by applying blue light in dermatology. 154 Phthalocyanines have also found space in PDT for melanoma cancer treatment; for instance, Castro and collaborators (2022) modified Zn( ii ) phthalocyanines with thiopyridinium units, finding that upon red light irradiation, murine melanoma cell viability decreased significantly, challenging the employed viability kit detection limit. 155 As these are briefly described, it is possible to find multiple pieces of literature regarding this point; it is recommended that the following works be revised.…”
Section: Cytotoxicity Associated With Photopolymerized Biomaterialsmentioning
confidence: 99%